Hybrid system for presidential and vice presidential elections in realising constitutional representation - Agrimiandra, Figgi; Pangestu, Ilham Aji; Lestari, Tiara Ayu (Jurnal Geuthèë: Penelitian Multidisiplin, 2024)
The research aims to analyze current presidential and vice presidential election systems, and has not yet been able to establish representative coexists, nor can it identify other models in the presidential election and vice president elections that could produce constitutional representation. This study is a normative-law study with a prescriptive nature. The approach used in the study is the approach to the legislation (conceptual approach), the conceptual approach (approach approach) and the comparative approach (approach), with a study of legal materials through library research). The study suggests that a hybrid election system, combining nominations by political parties and independent candidates, could better reflect the people's will and align with Constitutional principles. Such a system is more consistent with Modern Democracy, potentially leading to leaders with greater accountability and integrity. To address these issues, the author recommends implementing a hybrid system for the election of the President and Vice President to better realize constitutional representation. Additionally, there is a need to reconstruct the nomination process for presidential candidates in Indonesia to ensure a more representative and democratic election process. By adopting these changes, Indonesia can better align its presidential election system with democratic values and constitutional mandates.